Effect of arch support insole on plantar pressure distribution in females with mild and moderate hallux valgus - Maedeh Farzadi; Zahra Safaei-Pour; Seyyed Mohammad Ebrahim Mousavi; Hassan Saeedi; Marjan Farzi (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: Hallux Valgus is one of the most foot deformities which increase plantar pressure beneath big toe and first metatarsal. The aim of this study was to assess the effect of foot orthosis on plantar pressure distribution in subjects with mild and moderate Hallux Valgus. Materials & Methods: in this quasi-experimental study, females 16 with Hallux Valgus were recruited. Plantar pressure in 8 area of foot was measured by Pedar-X insole when wearing standard shoe only shoe with foot orthosis and shoe with foot orthosis after a month of using orthosis. Data were analyzed by repeated measure analysis of variance test. Results: using foot orthosis for a month leaded to decrease pressure in the big toe (P<0/019) first metatarsal and 3-5 metatarsals (P<0.001) and also increased pressure in medial mid foot (P<0.001). Conclusion: Foot orthosis decreased peak pressure in fore foot and increased it in medial mid foot. Therefore redistribute plantar pressure to the more normal pattern in Hallux Valgus subjects. So it could be one of the effective methods to prevent the progression of this deformity in its initial steps of formation.